Clinicopathological features and prognostic factors associated with gastroenteropancreatic mixed neuroendocrine non-neuroendocrine neoplasms in Chinese patients - Huang, Yu-Chen (World J Gastroenterol, 2021)
BACKGROUND: The incidence of mixed neuroendocrine-non-neuroendocrine neoplasms (MiNEN) is low. To improve our understanding of this rare tumor type and optimally guide clinical treatment, associated risk factors, clinical manifestations, and prognosis must be explored. AIM: To identify risk factors that influence the prognosis of patients with gastroenteropancreatic MiNEN (GEP-MiNEN). METHODS: We retrospectively analyzed the clinical data of 46 patients who were diagnosed with GEP-MiNEN at the First Affiliated Hospital of Bengbu Medical College (Anhui, China) between January 2013 and December 2017. Risk factors influencing the prognosis of the patients were assessed using Kaplan-Meier curves and cox regression models. We compared the results with 55 randomly selected patients with gastroenteropancreatic GEP neuroendocrine tumors, 47 with neuroendocrine carcinomas (NEC), and 58 with poorly differentiated adenocarcinoma. RESULTS: Among the 46 patients with GEP-MiNEN, thirty-five had gastric tumors, nine had intestinal tumors (four in the small intestine and five in the colon and rectum), and two had pancreatic tumors. The median age of the patients was 66 (41-84) years, and the male-to-female ratio was 2.83. Thirty-three (71.7%) patients had clinical stage III and IV cancers. Distant metastasis occurred in 14 patients, of which 13 had metastasis to the liver. The follow-up period was 11-72 mo, and the median overall survival was 30 mo. Ki-67 index ≥ 50%, high proportion of NEC, lymph node involvement, distant metastasis, and higher clinical stage were independent risk factors affecting the prognosis of patients with GEP-MiNEN. The median overall survival was shorter for patients with NEC than for those with MiNEN (14 mo vs 30 mo, P = 0.001), but did not significantly differ from those with poorly differentiated adenocarcinoma and MiNEN (30 mo vs 18 mo, P = 0.453). CONCLUSION: A poor prognosis is associated with rare, aggressive GEP-MiNEN. Ki-67 index, tumor composition, lymph node involvement, distant metastasis, and clinical stage are important factors for patient prognosis.